Analisis Kontribusi Usaha Ternak Domba Terhadap Pendapatan Peternak di Kecamatan Kertajati Kabupaten Majalengka - Denis Nuryadi; ulfa Indah Laela Rahmah; Lili Adam Yuliandri (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2024)
This research aims to determine the analysis of household income, the contribution of sheep farming to farmer income, and the factors that influence the size of the contribution of sheep farming. This research was carried out from June to August 2022. The analytical methods used were descriptive analysis, contribution analysis and multiple linear regression analysis. Respondents were determined using a purposive sampling method of 85 respondents. The variables observed were the number of working hours, number of workers, and number of livestock. The research results show that the average income of sheep farming is IDR 2.289.513/year. Meanwhile, the average income from breeders' business is IDR 7.730.746 /year. The sheep farming business contributes 29.61% to the total income of farmers in Kertajati District, Majalengka Regency. The coefficient of determination (R2) was obtained at 0.039. which means that the number of livestock, the amount of working hours, and the number of workers influence the contribution of sheep livestock by 3.9%, so Y is influenced by 96.1% by other factors outside the independent variable.